1997
DOI: 10.1016/s0092-8674(01)80015-5
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Roof Plate and Its Resident TGFβ-Related Proteins in Neuronal Patterning in the Dorsal Spinal Cord

Abstract: Distinct neuronal cell types are generated at characteristic times and positions in the dorsal horn of the spinal cord. We provide evidence that the identity and pattern of generation of dorsal neurons depend initially on BMP-mediated signals that derive from the epidermal ectoderm and induce dorsal midline cells of the roof plate. Roof plate cells provide a secondary source of TGFbeta-related signals that are required for the generation of distinct classes of dorsal interneurons. These inductive interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
487
1
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(508 citation statements)
references
References 57 publications
17
487
1
3
Order By: Relevance
“…In the hindbrain, they are expressed in a segmental manner in the dorsolateral region (Ando et al, 2005;Seth et al, 2006). Because this expression pattern is similar to the immunostaining pattern of the zn-5 antibody, which recognizes the cell adhesion molecule DM-GRASP (Neurolin/Alcam) expressed by the commissural neurons located in the rhombomere boundaries (Fashena and Westerfield, 1999;Trevarrow et al, 1990), we performed double immunostaining of the coronal sections of the hindbrain with the zn-5 and Lhx2/9 antibodies (Liem et al, 1997). We observed that the dorsolateral cluster of neurons expresses both the zn-5 antigen and Lhx2/9 (Fig.…”
Section: Two Distinct Classes Of Neurons In the Dorsal Hindbrain Basementioning
confidence: 95%
See 1 more Smart Citation
“…In the hindbrain, they are expressed in a segmental manner in the dorsolateral region (Ando et al, 2005;Seth et al, 2006). Because this expression pattern is similar to the immunostaining pattern of the zn-5 antibody, which recognizes the cell adhesion molecule DM-GRASP (Neurolin/Alcam) expressed by the commissural neurons located in the rhombomere boundaries (Fashena and Westerfield, 1999;Trevarrow et al, 1990), we performed double immunostaining of the coronal sections of the hindbrain with the zn-5 and Lhx2/9 antibodies (Liem et al, 1997). We observed that the dorsolateral cluster of neurons expresses both the zn-5 antigen and Lhx2/9 (Fig.…”
Section: Two Distinct Classes Of Neurons In the Dorsal Hindbrain Basementioning
confidence: 95%
“…The primary antibodies were used at the following dilutions: zn-5 (1:500, mouse monoclonal; Oregon Monoclonal Bank; Trevarrow et al, 1990;Fashena and Westerfield, 1999), Lhx2/9 (1:5,000, rabbit polyclonal; kindly provided by T.M. Jessell, Columbia University; Liem et al, 1997), GFP (1:500, rabbit polyclonal; MBL, Japan), and Gad1/2 (1:500, mouse monoclonal; Affiniti, UK). We used three excitation wavelengths (with Alexa 488, 546, and 647) for observation of goat Alexa-conjugated anti-mouse or anti-rabbit IgG secondary antibodies (1:1,500, Molecular Probes).…”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
“…We also assessed whether there were changes in the expression of postmitotic neuronal cell-type markers ( Fig. 2F; Liem et al, 1997;Briscoe et al, 2000). At stage 23, there was no apparent change in the expression boundaries of postmitotic cell populations of ISL-1 ϩ motor neurons or dorsal D2 interneurons, LIM-3 ϩ motor neurons, CHX-10 ϩ V2 interneurons, EN-1 ϩ V1 interneurons, or LH2 ϩ D1 interneurons (Fig.…”
Section: Overexpression Of Full-length and Truncated Crim1 In The Devmentioning
confidence: 99%
“…This requirement is partly mediated by members of the transforming growth factor-beta (TGF-␤) superfamily, particularly the bone morphogenetic protein (BMP) and closely related growth and differentiation factor (GDF) subfamilies (Lee and Jessell, 1999). Several BMPs/GDFs are secreted from the lateral margin of the neural plate, and subsequently by the overlying ectoderm and dorsal roof plate (Basler et al, 1993;Liem et al, 1995Liem et al, , 1997Lee et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…8,15,16 A BMP activity gradient across the D-V axis of the NT induces dorsal identity markers indicative of neural crest or dorsal interneuron precursors. [17][18][19][20] BMPs also induce apoptosis in the early developing central nervous system (CNS), [16][17][18][19][20][21] neuronal differentiation in mid-gestation of CNS precursors 22,23 and glial differentiation in late embryonic or adult CNS precursors. 24 Here, we investigate the possibility that locally produced extracellular factors, such as BMP and its antagonists, are involved in the regulation of cell numbers in the NT either by driving cells into the cell cycle or by controlling PCD.…”
Section: Introductionmentioning
confidence: 99%